Dental College of Georgia teams up with Richmond County Health Department to help - Nancy Wilson; Mark Peacock; Christopher Cutler; Jamie De Stefano (Georgia Southern University, 2017)
Background: The Central Savannah River Area remains, for many of the poor, a dental health care shortage area. Each year, from December to March, fourth-year dental students perform outreach with faculty to search the community for unmet dental needs, including dental caries and periodontal disease, the treatment of which is required for the Central Regional Dental Testing Service (CRDTS) Exam, the dental licensing examination. Methods: Fourth year students at the Augusta University Dental College of Georgia recruit patients for free dental pre-screenings at health fairs, community centers, the Barnyard Flea Market, and the dental school. Persons with periodontitis are invited for further screenings at the dental school where they receive a free dental examination and dental radiographs. Many of these patients present with other dental needs requiring restorations, root canals, and extractions, conditions that potentially could disqualify them from receiving periodontal therapy during CRDTS. Through a collaborative effort with the Richmond County Health Department Dental Clinic, these patients receive the treatment for their acute dental needs, while also qualifying them for the periodontics portion of the exam. Results: Regardless of their qualification status for boards, the program provides referrals for patients to the Dental College of Georgia or the Richmond County Health Department, gives patients a chance to be informed about their oral health status, and gives qualifying patients the potential to receive discounted or even free dental work. The efforts of the senior dental students represent an oral public health service effective in achieving improvements in periodontal outcomes within our community. Conclusions: This program not only benefits the future dentists of Georgia by helping provide licensing board requirements, it also introduces dental students to a more diverse population and provides exposure to public health outreach. In addition, this program offers a valuable service to underserved populations who would otherwise have limited or no access to dental care.